"Build a wall". "Tax a shed". "Fix a debt limit". The constructive and destructive potential of populist anti-statism and "naïve" statism. (4th May 2018) - Dunleavy, Patrick
ABSTRACT: Populist surges, movements and parties often centre around radically simplifying policy proposals, sometimes anti-statist in intent (e.g. fix a limit to state borrowing in cash terms), and at other times pushing naïve statist solutions (e.g. build a giant wall to keep out migrants; or tax companies' activities in a given shed, not their profits). Most liberal political science condemns the crudity and often unrestrained vigour of populist "solutions". But on occasion, they can have value in counteracting the increasing complexities that elites often build into public policies. Two case studies show populist pressure for simplification working effectively in one instance – the "tax shaming" campaign against multinationals avoiding corporation taxes; and engendering only disorder in another instance – the effort to enforce national debt limits in nominal terms in the USA.